2017
DOI: 10.1371/journal.pone.0179148
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the species Malassezia pachydermatis and re-evaluation of its lipid dependence using a synthetic agar medium

Abstract: The genus Malassezia includes lipophilic yeasts, which are part of the skin microbiota of various mammals and birds. Unlike the rest of Malassezia species, M. pachydermatis is described as non-lipid-dependent, as it is able to grow on Sabouraud glucose agar (SGA) without lipid supplementation. In this study we have examined the phenotypic variability within M. pachydermatis and confirmed its lipid-dependent nature using a synthetic agar medium. We used a selection of representative non-lipid-dependent strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…Traditionally, the lipid-dependent species were thought to occur only on human skin, while M. pachydermatis was assumed to be restricted to animals skin and in particular carnivores [ 39 ]. It is suspected, that other Malassezia species, like M. globosa or M. sympodialis or even lipid-dependent strains of M. pachydermatis could be involved in developing of otitis in dogs, but we were not able to cultivate them [ 40 , 41 ]. Mentioned species were also isolated from the skin of healthy cats [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the lipid-dependent species were thought to occur only on human skin, while M. pachydermatis was assumed to be restricted to animals skin and in particular carnivores [ 39 ]. It is suspected, that other Malassezia species, like M. globosa or M. sympodialis or even lipid-dependent strains of M. pachydermatis could be involved in developing of otitis in dogs, but we were not able to cultivate them [ 40 , 41 ]. Mentioned species were also isolated from the skin of healthy cats [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In quantitative investigations of the skin flora, the culture medium is known to have significant effects on the counts of Malassezia yeasts derived from human skin, prompting analogous canine studies. Amongst Malassezia spp., M. pachydermatis is the least fastidious and normally grows readily on routine media such as SDA, although M. pachydermatis variants with more‐exacting lipid requirements have been isolated …”
Section: Quantification Of Malassezia Populations On Canine and Felinmentioning
confidence: 99%
“…In early qualitative studies, the addition of 1% Tween 80 to a dextrose/ yeast extract agar enhanced the isolation of M. pachydermatis . Tween 80 was not needed for the selective and differential isolation of M. pachydermatis in the presence of peptone, now recognised as the essential lipid source for growth of that species on SDA . Malassezia pachydermatis was isolated from swab wash samples in comparable numbers after three and seven days of incubation at 32°C on each of five media; SDA, SDA plus 1% Tween 80, Ushijima's medium A, modified Dixon's agar and Leeming's medium .…”
Section: Quantification Of Malassezia Populations On Canine and Felinmentioning
confidence: 99%
“…Historically M. pachydermatis was regarded as being "lipophilic but not lipid-dependent" because it was the only member of the genus to grow on Sabouraud's dextrose agar (Guillot and Bond, 1999). Recently, genome sequencing has confirmed that M. pachydermatis lacks a fatty acid synthase gene like the other members of the genus (Wu et al, 2015), but is uniquely able to utilize lipid fractions within the peptone component of Sabouraud's dextrose agar for growth (Puig et al, 2017). These observations explain its failure to grow on lipidfree defined media and thus M. pachydermatis should now also be regarded as being "lipid-dependent" (Puig et al, 2017).…”
Section: Recent Re-assessments Of Lipid-dependence In Malassezia Pachmentioning
confidence: 99%